Geriatric Emergency Medicine Educational Module: Abdominal Pain in the Older Adult - Gerson, Lowell; Losman, Eve (Academic emergency medicine, 2009)
The Society for Emergency Medicine (SAEM) Geriatrics Task Force has created an instructional tool to address the complaint of abdominal pain in older adults presenting to the emergency department (ED). This is the first module in a comprehensive, web‐based geriatric emergency medicine curriculum that will address common syndromes in older adults presenting to the ED. There is no formal, residency‐based curriculum in geriatric emergency medicine and there is a paucity of geriatric Continuing Medical Education (CME) opportunities for practicing emergency physicians. The amount, quality, and convenience of geriatrics training available to emergency physicians is insufficient. This educational gap is particularly concerning given the ever‐growing volume of older adult emergency patients. The Task Force chose to focus first on geriatric abdominal pain because a survey of emergency physicians in the mid 1990s found that it is one of the most difficult complaints to evaluate and manage. The module comprises of six clinical cases with a pre‐ and post‐test. Together, these cases encompass the broad differential diagnosis for geriatric abdominal pain and the core medical knowledge pertaining to the subject. The modules will expose the learner, through either content or modeling, to the six Accreditation Council for Graduate Medical Education (ACGME) core competencies and to the Principles of Geriatric Emergency Medicine including rapid evaluation of functional status, communication skills, and consideration of the effect of polypharmacy and co‐morbidity on the presenting complaint. This module will be available to residency programs as an “asynchronous educational session” via the Council of Emergency Medicine Residency Directors (CORD) website as well as to practicing emergency physicians via the SAEM and American College of Emergency Physicians (ACEP) websites.